Circ_0001665 Contributes to the Occurrence of Vestibular Schwannoma via Targeting miR-302a-3p/Adam9/EGFR Signaling Pathway. (10th May 2022) - Wu, Lihua; Wang, Yinfang; Liu, Qinghua; Wu, Jianman; Zheng, Hao; Lin, Biyu; Huang, Shaopeng
Highlights: The characterization of circ_0001665. Circ_0001665 deficiency suppresses cell proliferation and prompts cell apoptosis in VS. Adam9 is regulated by circ_0001665 and activates EGFR signaling pathway. Abstract: Vestibular schwannoma (VS) is a benign, slow-growing neoplasm, which is an important cause of sensorineural hearing loss. Circular RNAs (circRNAs) have been widely reported to be dysregulated and participate in multiple biological processes of human diseases. However, roles of most circRNAs still remain explored. In the present study, the main aim was to uncover the impacts of circ_0001665, a cricRNA derived from ADAM metallopeptidase domain 9 (Adam9), on the biological behaviors of VS cells. Firstly, RT-qPCR was done to analyze circ_0001665 expression in VS cells and it was suggested that circ_001665 was distinctly up-regulated in rat VS cells. Supported by western blot analysis, circ_0001665 inhibition was validated to impede the proliferation while inducing the apoptosis of VS cells via functional assays. Additionally, results of mechanism assays demonstrated that circ_0001665 could function as a sponge of microRNA-302a-3p (miR-302a-3p) to enhance Adam9 expression and to activate EGFR signaling pathway in VS cells. Eventually, it was indicated in rescue assays that circ_0001665 expedited proliferation and restrained apoptosis of VS cells via modulation on miR-302a-3p/Adam9. Collectively, our study identified a novel perspective for exploration into molecular mechanisms in VS.